Of Fallacies and Curricula: A Case of Business Ethics - Acevedo, Alma (Teaching business ethics, 2001)
One of the main objectives of the undergraduate business school curriculum is to develop the students' critical thinking and decisionmaking skills. Official documents such as the school's objectives usually state this as part of its social contract. However, university processes sometimes break the most elementary rules of logical reasoning which, in turn, may lead to questionable decisions. This paper discusses the specific case of the mandatory stand-alone business ethics course as an instance of flawed reasoning in curricular processes. Educational institutions model the students' decision making patterns, not only by formal courses but by the example their own decision making processes set. Academicians should be aware of these processes' underlying values and vices. This should lead to better decisions and set a proper example for our students.